Вплив попередньої обробки волотей на морфогенез в культурі пиляків Oryza sativa L. - Шестопал, О.Л.; Замбріборщ, І.С.; Ігнатова, С.О.; Шпак, Д.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. Study of the influence pretreatment of panicle on morphogenic potential of microspores in anther culture of rice. Methods. Obtaining of rice double haploid lines by anther culture in vitro. The statistical methods. Results. The influence different variants pretreatment of rice panicle on the processes of induction and regeneration in anther culture of rice were studied. The 218 green plants-regenerants were received. Conclusions. To increase the formation of embryo like structures in anther culture of rice panicles should be incubated for the pretreatment in water at 6–8°C during 3–7 days. The positive effect on the formation of embryoides and sufficient amount of green regenerants and the low formation albino regenerants from using the cold pretreatment of panicle by solution abscisic acid (0.5 mg/L) were showed.